Eksistensi dan Kewenangan Mahkamah Syar’iyah dalam Mengadili Tindak Jinayah di Provinsi Nanggroe Aceh Darussalam - Abror, Nashihul (Al-Jinayah : Jurnal Hukum Pidana Islam, 2020)
The existence of the Syar'iyah Court in Aceh Darussalam Province is very appealing. Particularly related to (1) the State of Indonesia which is not an Islamic State, and (2) its enforcement from the perspective of fiqh siyasah. The conclusion of this paper inferred that firstly; the background of the Syar'iyah Court in DI Province of Aceh, which has existed since the Japanese era, is not only a gift from the central government to the people of Aceh through the Regional Autonomy Law and the existence of Law No. 44 of 1999 alone, but is more of a return to the rights of the Aceh people that have been lost. Secondly: the Syar'iyah Court has the authority to work and examine, decide, and settle cases at the first level, in the fields of ahwal al-syakhshiyah, Mu'amalah, and Jinayah. Thirdly: the existence of the Mahkmah Syar'iyah is a demand from every Muslim community to resolve various problems that occur as practiced by the Prophet, as well as based on QS al-Nisa '(4) 105, and manifested by the Shari'iyah Court in NAD whose main task is the implementation of Islamic law.